Evolution Inclusions and Variation Inequalities for Earth Data Processing III Long-Time Behavior of Evolution Inclusions Solutions in Earth Data Analysis - Zgurovsky, Mikhail Z.; Kasyanov, Pavlo O.; Kapustyan, Oleksiy V.; Valero, José; Zadoianchuk, Nina V. (Advances in Mechanics and Mathematics, 2012)
In this sequel to two earlier volumes, the authors now focus on the long-time behavior of evolution inclusions, based on the theory of extremal solutions to differential-operator problems. This approach is used to solve problems in climate research, geophysics, aerohydrodynamics, chemical kinetics or fluid dynamics. As in the previous volumes, the authors present a toolbox of mathematical equations. The book is based on seminars and lecture courses on multi-valued and non-linear analysis and their geophysical application.